Dynamics of NAD-metabolism: everything but constant. (27th November 2015) - Opitz, Christiane A.; Heiland, Ines
Abstract : NAD, as well as its phosphorylated form, NADP, are best known as electron carriers and co-substrates of various redox reactions. As such they participate in approximately one quarter of all reactions listed in the reaction database KEGG. In metabolic pathway analysis, the total amount of NAD is usually assumed to be constant. That means that changes in the redox state might be considered, but concentration changes of the NAD moiety are usually neglected. However, a growing number of NAD-consuming reactions have been identified, showing that this assumption does not hold true in general. NAD-consuming reactions are common characteristics of NAD + -dependent signalling pathways and include mono- and poly-ADP-ribosylation of proteins, NAD + -dependent deacetylation by sirtuins and the formation of messenger molecules such as cyclic ADP-ribose (cADPR) and nicotinic acid (NA)-ADP (NAADP). NAD-consuming reactions are thus involved in major signalling and gene regulation pathways such as DNA-repair or regulation of enzymes central in metabolism. All known NAD + -dependent signalling processes include the release of nicotinamide (Nam). Thus cellular NAD pools need to be constantly replenished, mostly by recycling Nam to NAD + . This process is, among others, regulated by the circadian clock, causing complex dynamic changes in NAD concentration. As disturbances in NAD homoeostasis are associated with a large number of diseases ranging from cancer to diabetes, it is important to better understand the dynamics of NAD metabolism to develop efficient pharmacological invention strategies to target this pathway.